Elevation of FVIII: C in Venous Thromboembolism Is Persistent and Independent of the Acute Phase Response - O’Donnell, James; Mumford, Andrew D.; Manning, Richard A.; Laffan, Michael (Thrombosis and Haemostasis, 2000)
Recent literature has suggested a role for elevated FVIII:C in venous thromboembolic disease (VTED). However since FVIII:C is known to rise in response to an acute phase reaction, it is difficult to determine whether the increased FVIII:C precedes the thrombosis or represents a secondary reactive phenomenon. In an attempt to address this question, we followed 35 patients with confirmed VTED, raised FVIII:C level (>1.5 iu/ml) and no other thrombotic tendency. Serial measurements of FVIII:C, vWF:Ag, C-reactive protein and fibrinogen were performed. We hypothesized that a persistent increase in FVIII:C in the absence of any other measures of ongoing acute phase response, would support the idea that elevation of FVIII:C is a constitutional phenomenon.Of this initial group, 94% continued to have an elevated FVIII:C level throughout the period of follow up (median 8 months; range 3 to 39 months), with no significant difference between the FVIII:C levels determined at first estimation and those obtained during follow up (p = 0.58). Conversely, only 18% had evidence of an acute phase reaction when first assessed, and nonparametric ranking analysis demonstrated no correlation between FVIII:C and either C-reactive protein or fibrinogen (p = 0.315 and 0.425 respectively).We conclude that increased FVIII:C levels following VTED are persistent, independent of the acute phase reaction, and thus may represent a constitutional risk factor for VTED.
Keywords: FVIII:C; venous thromboembolism; acute phase